Use of Digital Droplet PCR to Detect Mycobacterium tuberculosis DNA in Whole Blood-Derived DNA Samples from Patients with Pulmonary and Extrapulmonary Tuberculosis - Yang, Jiaru; Han, Xinlin; Liu, Aihua; Bai, Xiyuan; Xu, Cuiping; Bao, Fukai; Feng, Shi; Tao, Lvyan; Ma, Mingbiao; Peng, Yun (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis (TB) is a chronic infectious disease that has been threatening public health for many centuries. The clinical diagnostic procedure for TB is time-consuming and laborious. In the last 20 years, real-time fluorescence-based quantitative PCR (real-time PCR) has become a better alternative for TB diagnosis in clinics due to its sensitivity and specificity. Recently, digital droplet PCR (ddPCR) has been developed, and it might be an ideal alternative to conventional real-time PCR for microorganism detection. In this study, we aimed to assess the capacity of ddPCR and qreal-time PCR for detecting low levels of circulating Mycobacterium tuberculosis (MTB) DNA. The study involved testing whole blood samples for an MTB DNA target (known as IS6110). Blood samples were obtained from 28 patients with pulmonary TB, 28 patients with extrapulmonary TB, and 28 healthy individuals. The results show that ddPCR could be used to measure low levels of MTB DNA, and it has the potential to be used to diagnose pulmonary and extrapulmonary TB based on clinical samples.